Interplay of Carbonic Anhydrase IX With Amino Acid and Acid/Base Transporters in the Hypoxic Tumor Microenvironment - Venkateswaran, Geetha; Dedhar, Shoukat (Frontiers in Cell and Developmental Biology, 2020)
Solid tumors are challenged with a hypoxic and nutrient-deprived microenvironment. Hence, hypoxic tumor cells coordinatively increase the expression of nutrient transporters and pH regulators to adapt and meet their bioenergetic and biosynthetic demands. Carbonic Anhydrase IX (CAIX) is a membrane-bound enzyme that plays a vital role in pH regulation in the tumor microenvironment (TME). Numerous studies have established the importance of CAIX in mediating tumor progression and metastasis. To understand the mechanism of CAIX in mediating tumor progression, we performed an unbiased proteomic screen to identify the potential interactors of CAIX in the TME using the proximity-dependent biotin identification (BioID) technique. In this review, we focus on the interactors from this BioID screen that are crucial for nutrient and metabolite transport in the TME. We discuss the role of transport metabolon comprising CAIX and bicarbonate transporters in regulating intra- and extracellular pH of the tumor. We also discuss the role of amino acid transporters that are high confidence interactors of CAIX, in optimizing favorable metabolic state for tumor progression, and give our perspective on the coordinative interplay of CAIX with the amino acid transporters in the hypoxic TME.